2017
DOI: 10.2147/bctt.s148080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on breast cancer recurrence and mortality: a review

Abstract: Statins, or 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, are medications that have been used for decades to lower cholesterol and to prevent or treat cardiovascular diseases. Since their approval by the US Food and Drug Administration in the 1980s, other potential uses for statins have been speculated on and explored. Basic science and clinical research suggest that statins are also effective in the management of breast cancer. Specifically, in various breast cancer cell lines, statins increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 46 publications
(40 reference statements)
3
72
0
3
Order By: Relevance
“…Indeed, upregulation of cholesterol synthesis positively correlates with a decline in patient survival (Kuzu, Noory, and Robertson, ; Weinstein et al, ). The important role of cholesterol in cancer progression is further supported by research that found that the use of statins can have a protective effect against the advancement of certain cancers such as liver, gastrointestinal, prostate, and breast (Singh and Singh, ; Stryjkowska‐Góra et al, ; Van Wyhe et al, ). Due to this dependence on cholesterol, cancer cells might be more responsive to drugs targeting the cholesterol synthesis pathway than normal healthy cells.…”
Section: Mechanismmentioning
confidence: 95%
“…Indeed, upregulation of cholesterol synthesis positively correlates with a decline in patient survival (Kuzu, Noory, and Robertson, ; Weinstein et al, ). The important role of cholesterol in cancer progression is further supported by research that found that the use of statins can have a protective effect against the advancement of certain cancers such as liver, gastrointestinal, prostate, and breast (Singh and Singh, ; Stryjkowska‐Góra et al, ; Van Wyhe et al, ). Due to this dependence on cholesterol, cancer cells might be more responsive to drugs targeting the cholesterol synthesis pathway than normal healthy cells.…”
Section: Mechanismmentioning
confidence: 95%
“…) . According to experimental and epidemiologic data, statins have been found to suppress tumour progression as well as incidence of BC . Mechanistically, statins are able to actively inhibit cholesterol synthesis thereby attenuating cell proliferation .…”
Section: Cholesterol Lowering For Cancer Therapy: Available Choicesmentioning
confidence: 99%
“…Recently, the cholesterol lowering-independent or "pleiotropic" effects of statins have gained greater recognition, particularly in the area of cancer therapeutics (7). Cumulative in vivo evidence as well as observational clinical studies suggest a therapeutic potential of statins in different cancer models (17). Nevertheless, translating these findings into clinical studies faces multi-dimensional challenges comprising; which statin to use, the timing (when or at what stage of cancer progression), the temporal frame (short-term versus long-term), and what cytotoxic agents/chemotherapy line, hormonal, or radiotherapy with which should a particular type of statin is co-administered.…”
Section: Discussionmentioning
confidence: 99%
“…Although not universally accepted as the standard treatment for MBC (16), vinorelbine in combination with carboplatin is adapted in the clinical practice for MBC patients in "Al-Baironi" the major oncology Hospital in Syria. Since inflammation is a critical component of tumor progression, and due to the well-established anti-inflammatory properties of statins (17), we sought to investigate the impact of statins on some inflammatory markers (highsensitivity C-reactive protein (hsCRP), lactate dehydrogenase (LDH)) and their prognostic potential in predicting therapeutic outcomes in MBC.…”
mentioning
confidence: 99%